2009
DOI: 10.1111/j.1439-0272.2008.00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of vardenafil versus sertraline in the treatment of premature ejaculation: a randomised, prospective and crossover study

Abstract: We investigated safety and efficacy of vardenafil and sertraline in premature ejaculation (PE). Seventy-two men graded their primary PE on a scale of 0-8 (0 = almost never, 8 = almost always). Intravaginal ejaculatory latency time (IELT) was measured. Patients were included if they scored their PE as 4 or greater and their IELTs were less than 1.30 min. After 6 weeks of behavioural psychosexual therapy, 49 patients still had a PE of 4 or greater and an IELT less than 1.30 min and they were randomised: 6 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 34 publications
0
55
0
2
Order By: Relevance
“…Vardenafil: Recent small studies in men with lifelong PE compared vardenafil (Aversa et al, 2009) or sertraline in a randomized, prospective, crossover design (Mathers et al, 2009) and showed an increase in IELT as well as improvement in outcome measures with vardenafil as requested by the patient. In a laboratory setting, PDE5i seem to prolong the median duration of vibratory stimulation (ELT), but the difference from placebo was significant with vardenafil (P < 0.001).…”
Section: Pde5 Inhibitors (Pde5i)mentioning
confidence: 99%
“…Vardenafil: Recent small studies in men with lifelong PE compared vardenafil (Aversa et al, 2009) or sertraline in a randomized, prospective, crossover design (Mathers et al, 2009) and showed an increase in IELT as well as improvement in outcome measures with vardenafil as requested by the patient. In a laboratory setting, PDE5i seem to prolong the median duration of vibratory stimulation (ELT), but the difference from placebo was significant with vardenafil (P < 0.001).…”
Section: Pde5 Inhibitors (Pde5i)mentioning
confidence: 99%
“…56 Two studies of vardenafil for PE showed that it increases IELT and reduces the post-ejaculation refractory period in men with lifelong PE. 58,59 A double-blind, prospective, crossover study compared the effectiveness of sildenafil with the squeeze technique and on-demand use of two different SSRIs (paroxetine and sertraline) and clomipramine in patients with primary PE. Sildenafil demonstrated a 15-fold increase in IELT compared with two-to fourfold increases for the other groups.…”
Section: Pde-5ismentioning
confidence: 99%
“…Mathers et al 43 reported that PE grade improved by 2.7 points in the vardenafil group vs 1.9 points in the sertraline group, and IELT increased by 5 min in the vardenafil group and by 3 min in the sertraline group. Wang et al 44 demonstrated the superiority of sildenafil vs paroxetine and squeeze technique, as well as Abdel-Ahmid et al, 45 who challenged patients with clomipramine and sertraline also.…”
Section: Pde5-i In Pementioning
confidence: 99%